PENDEKATAN PREVENTIF DALAM MENANGGULANGI KARIES - Edi Hartini Sundoro (Faculty of Dentistry, Universitas Indonesia, 2015)
Treatment of caries lesions has been shifted to a preventive approach and the recommended measures by the WHO are clinical and radiological examination to detect early lesions and cavities, evaluation of caries risk factors, management of these factors, treatment of caries lesions and formulation of maintenance program. The how and why of this preventive approach will be briefly viewed.